2008
DOI: 10.1118/1.2921129
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive in vivo tomographic optical imaging of cellular morphology in the breast: Possible convergence of microscopic pathology and macroscopic radiology

Abstract: This article presents a pilot study of multispectral diffuse optical tomography for noninvasively imaging volume fraction and mean size of cellular scattering components in the breast. Cellular morphology images for a total of 14 cases ͑four malignant breast and ten benign lesions͒ were obtained. Analyzing the images based on the pathological findings of the cases studied, we found that light scattering in the breast was contributed from both the nucleus and organelles such as mitochondria and nucleolus. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…A 2008 paper by Li et al [49] has reported significant differences in the mean size and volume fraction of cellular scattering components between benign and malignant lesions. The calculated global averages for malignancies are [HbT]=(65±34) µM and SO 2 =(66±24) % (from ten published studies) [45].…”
Section: Optical Properties Of Breast Diseasementioning
confidence: 98%
“…A 2008 paper by Li et al [49] has reported significant differences in the mean size and volume fraction of cellular scattering components between benign and malignant lesions. The calculated global averages for malignancies are [HbT]=(65±34) µM and SO 2 =(66±24) % (from ten published studies) [45].…”
Section: Optical Properties Of Breast Diseasementioning
confidence: 98%
“…Based on clinical data, a significant contrast ratio in the mean cellular size and the volume fraction between malignant and benign lesions has been found. 5,6 Accordingly, malignant tissues have shown increased mean values of the reduced scattering coefficients in comparison with the benign tissue. [7][8][9][10] Simultaneous reconstruction of absorption and scattering distributions of human breast has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…DOT has demonstrated clinical potential for distinguishing benign from malignant breast lesions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two of the estimated optical parameters used to characterize malignant and benign breast tissues are the absorption and scattering coefficients. By estimating these parameters that are obtained from multiwavelength imaging systems, it is possible to quantify tissue constituents such as oxygenated and deoxygenated hemoglobin, lipid and water concentrations, as well as structural parameters, which are linked to the dimensions and densities of the scattering centers.…”
Section: Introductionmentioning
confidence: 99%
“…Optical imaging techniques are promising candidates for such purpose since they are noninvasive and relatively inexpensive. [1][2][3][4][5] The basic idea is to analyze the spectrum of scattered light in order to extract morphologic information regarding the particles involved. In Ref.…”
Section: Introductionmentioning
confidence: 99%